Evaluation of a Diagnostic Algorithm Using Immunoglobulin M Enzyme-Linked Immunosorbent Assay To Differentiate Human West Nile Virus and St. Louis Encephalitis Virus Infections during the 2002 West Nile Virus Epidemic in the United States - Martin, Denise A. (American Society for Microbiology, 2004)
A diagnostic algorithm was developed to differentiate between human infections of West Nile virus (WNV) and St. Louis encephalitis virus (SLEV) using positive-to-negative (P/N) ratios derived from the immunoglobulin M capture enzyme-linked immunosorbent assay (MAC-ELISA). To validate this algorithm, we tested 1,418 serum and cerebrospinal fluid (CSF) samples from confirmed WNV and SLEV infections collected during the WNV epidemic of 2002 in the United States. WNV P/N-to-SLEV P/N ratios (W/S ratios) were calculated and used to identify the infecting virus. These results were compared to results from the plaque reduction neutralization test (PRNT), which is currently the standard assay used to discriminate between closely related flavivirus infections. If the W/S ratio was ≥1, the predictive value positive (PNP) for WNV was 97.8%, where 95% of flavivirus cases were due to WNV infection and only 3.7% of specimens would require PRNT to differentiate WNV from SLEV infection. Use of the W/S ratio as part of the testing algorithm to interpret MAC-ELISA results generates reportable probable cases quickly, alleviating the need for PRNT in most instances.